Analysis of Load Optimization in Solid Rocket Motor Propellant Grain with Pressure Cure - Zhanxin Cui; Haiyang Li; Zhibin Shen; Huiru Cui (International Journal of Aerospace Engineering)
At present, the casting of large-size motors often adopts pressure cure. This technology can effectively reduce the risk of damage to the structural integrity of the grain in the case-bonded casting solid rocket motor. In this paper, ABAQUS is used to establish a finite element model of star-shaped grains. The whole process of pressure cure was simulated and modeled, and the Python script was redeveloped. The Evol evolutionary algorithm was used in ISIGHT to optimize the load parameters such as pressure value, attenuation coefficient of the relief curve, and the attenuation coefficient of the cooling curve. The effects of different pressure values and different cooling and depressurizing rates on the residual stress and strain were analyzed. The optimization results show that the closer the pressure value is to the theoretical pressure, the more significant the effect of pressure cure. However, the effect of stress and strain reduction in different directions is slightly different. The different cooling and pressure relief rates have a great influence on the process quantity. Pressure cure works best when the pressure attenuation coefficient is equal to 6850, and the temperature attenuation coefficient is equal to 8650. The optimization analysis of pressure curing provides a reference for engineering practice.